2015
DOI: 10.1001/jamainternmed.2014.8012
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Multiple Blood Pressure Medications, Achieved Blood Pressure, and Mortality in Older Nursing Home Residents

Abstract: IMPORTANCE Clinical evidence supports the beneficial effects of lowering blood pressure (BP) levels in community-living, robust, hypertensive individuals older than 80 years. However, observational studies in frail elderly patients have shown no or even an inverse relationship between BP and morbidity and mortality. OBJECTIVE To assess all-cause mortality in institutionalized individuals older than 80 years according to systolic BP (SBP) levels and number of antihypertensive drugs. DESIGN, SETTING, AND PARTICI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
138
2
14

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(158 citation statements)
references
References 22 publications
4
138
2
14
Order By: Relevance
“…14,16,17 According to Japanese guidelines, 17 home blood pressure measurement is useful for preventing an excessive or insufficient antihypertensive effect of drugs. To our knowledge, the Predictive Values of Blood Pressure and Arterial Stiffness in Institutionalized Very Aged Population Study (PARTAGE) 18,19 is the only survey based on the self-measured blood pressure in octogenarians. High blood pressure did not entail an increased risk of all-cause mortality or major cardiovascular events.…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,16,17 According to Japanese guidelines, 17 home blood pressure measurement is useful for preventing an excessive or insufficient antihypertensive effect of drugs. To our knowledge, the Predictive Values of Blood Pressure and Arterial Stiffness in Institutionalized Very Aged Population Study (PARTAGE) 18,19 is the only survey based on the self-measured blood pressure in octogenarians. High blood pressure did not entail an increased risk of all-cause mortality or major cardiovascular events.…”
Section: Hypertensionmentioning
confidence: 99%
“…In view of the uncertainty about blood pressure targets to be achieved in the very elderly, we assessed the predictive value of the self-measured home blood pressure in octogenarians enrolled in the International Database on Home Blood Pressure in Relation to Cardiovascular Outcome (IDHOCO). 20 In line with the PARTAGE findings, 19 we stratified our analysis according to treatment status.…”
Section: Hypertensionmentioning
confidence: 99%
“…17,18 It has even been proposed that lowering BP in older persons using antihypertensive medication may decrease CBF. 3,[19][20][21] These observations have led to the suggestion that low BP in old age could result in cerebral hypoperfusion, initiated by impaired cerebral autoregulation. Nevertheless, in older persons with low BP at risk of impaired cerebral autoregulation, limited data are available as to whether CBF is in fact impaired.…”
mentioning
confidence: 99%
“…The Milan Geriatrics 75+ Cohort study [32] found that higher BPs among older outpatients were associated with higher levels of cognitive function (10mmHg increase in SBP associated with 0.26 point (95% CI 0.13 to 0.40) rise in MMSE score; median BP of cohort 145/80mmHg). The PARTAGE study, conducted on French and Italian nursing home residents (mean MMSE 23), found higher mortality in those with low SBP (defined as <130mmHg) receiving multiple BPlowering medications (HR 1.78 95% CI 1.34 to 2.37), after adjustment for cardiovascular comorbidities [33]. For individuals with established cognitive impairment, recent cross-sectional data identified an association between low daytime SBP (< 128mmHg) and greater decline in MMSE score (mean -2.8 [SD 3.8]), in those treated with antihypertensive medications [34].…”
Section: Epidemiological Considerationsmentioning
confidence: 99%